Lexical category influences in Persian children who stutter. (December 2013) - Vahab, Maryam; Zandiyan, Azadeh; Falahi, Mohammad Hadi; Howell, Peter
Abstract: This article explores the effect that words from different lexical categories have on disfluency in 12 Persian children, ten boys and two girls, who stutter. They were aged 7 years 5 months to 10 years 6 months. Words from the participants' narrative and reading samples (sub-tests of the Reading and Dyslexia Test validated for Persian school-aged children) were categorized as content, function, or content–function, and stuttering-like disfluencies were coded in each speech sample. Content and content–function words were significantly more likely to show stuttering-like disfluencies than function words. The distribution of symptom types over content and content–function words was similar, and differed from the distribution seen in function words. The symptom type analysis also supported the view that whole-word repetitions should not be grouped with other stuttering-like disfluencies.